KONSEP PENDIDIKAN PEMBEBASAN MANSOUR FAKIH - Rifa'i, Amir (Kelola: Journal of Islamic Education Management, 2019)
This research has purpose to discuss about the educational concept of Mansour Fakih’s liberation and the relevance with Islamic education. The expectation of this research’s result is to give a solution or an idea for the purpose of Islamic education. This research is an answer from the Mansour Fakih educational liberation’s question, and it uses qualitative research whereas the method is library research. The collecting data have been done by investigating Mansour Fakih’s work especially about education while the data analysis that is used is word analysis which will express some literature from the research’s object. The research’s result shows that: 1. The educational concept of Mansour Fakih’s liberation is about critical liberation education that can be concluded as the education that doesn’t restrict the pupils to develop their creativities with some characteristics that are learning from experiences, not teaching, and dialogis 2. The relevance of Mansour Fakih education with Islamic education. From the educational concept of Mansour Fakih’s liberation with Islamic education is that both of them do not wish for the education that restrict because human’s essence is free.